Japan in Intraregional Trade: Alternative Models - Koo, Anthony Y. C. (The Review of Economics and Statistics, 1955)
outside the range of attainment once full employment is reached. For even discarding the oft-used but spurious (for the problem at hand) historical average growth rate of 3-3Y2 per cent, the ceiling rate (with little inflation) seems to be in the neighborhood of 6-7 per cent. But if income cannot grow at the (adjusted) required rates, neither can induced investment, which by definition is dependent upon income growth for its achievement. At the very least, then, the accelerator is an extremely doubtful generator of growth. It is with such thoughts in mind that we assert (or reassert) the importance of innovational (autonomous) investment in providing, on the one hand, the principal generating force of periods of sustained growth, and on the other, because of its inherent irregularity, the primary source of unstable growth known as the (major) business cycle.